Istri Sebagai Pencari Nafkah dalam Pandangan Muhammad Quraish Shihab - Mustopa Kamal; Zaki Abdul Wahab; Nunu Nugraha (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
This study aims to find out the opinion of Muhammad Quraish Shihab about the wife who feeds the family, the legal basis used by Muhammad Quraish Shihab on the wife who feeds the family, and the method of ijtihad concerning the wife who provides for the family according to Muhammad Quraish Shihab. After analyzing the data, it is obtained that in the opinion of Muhammad Quraish Shihab that the law of the wife who provides for the family is permissible because not all types of work that existed in the present have existed at the time of the Prophet SAW. However, Islam confirms that women are active in various activities, or work during the work has no negative impact on him, and does not neglect the obligation of a wife in the household.